Georg Gruber : his contribution to music education in South Africa and an evaluation of selected vocal compositions and arrangements - Matier, Rosemary (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1991)
In this thesis I have given a factual account of Georg Gruber's contribution to music education in South Africa by giving a short biography and studying a) his philosophy of music education, b) the content of the music courses offered at Rhodes University during his occupancy of the Chair (1955-1972), c) the content of the music courses offered at the University of Fort Hare from 1974-1977, d) his contribution to choral education, e) his publications in the field of music education. I have given an evaluation of selected vocal compositions: a) Two masses, b) Terra Nova , c) Two African cantatas, i) Ukucula Ematola and ii) Izango ZakwaNtu , and seven arrangements of real folksongs from several different countries: a) Coventry Carol and Sweet Nightingale, b) Die Alibama, c) Merck tog hoe sterck, d) Entre Ie Boeuf et l'Ane gris, e) Aba Heidschi-bum-beidschi and f) Cheder Katan. Through the above study I have drawn conclusions regarding his compositional techniques prior to coming to South Africa as shown in the two mass compositions a nd the changes which occurred after being exposed to African music. The attention to detail in his arrangements and their sheer simplicity show his skill and craftsmanship also in this genre. Appendices of the works discussed have been submitted in a separate file and Appendix 8 lists all his available folksong arrangements.
Keywords: Gruber, Georg, 1904-1979; Musicians -- South Africa; Music teachers -- South Africa